2006
DOI: 10.1051/fruits:2006038
|View full text |Cite
|
Sign up to set email alerts
|

Élaboration d’une boisson à partir d’écart de triage de dattes : clarification par traitement enzymatique et microfiltration

Abstract: --Introduction. Despite their high nutritional value, by-products of dates are valueless in Tunisia, an important date-producing country. Our study aimed at testing a method for recovering these products by means of extraction, starting from a date paste, of a clarified drink. Materials and methods. The process of pulp extraction adopted was inspired by a traditional method. A rough solution obtained from the dilution of date paste was treated with enzymes (pectinases and cellulases) and by tangential microfil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
1
16
1
Order By: Relevance
“…A combination of pectinase and cellulase was used since the synergetic effect of these enzymes is well documented in literature for several fruit such as orange peel, dates and grapefruit peel (Cheikh-Rouhou, Baklouti, et al, 2006;Çinar, 2005;EspachsBarroso, Soliva-Fortuny, & Martín-Belloso, 2005;Wilkins, Widmer, Grohmann, & Cameron, 2007). In this study, the maximum of soluble solids recovery was reached when combining 50 U Table 4 Effect of pectinase and incubation time (min) on soluble solids yield (g of TSS/100 g) in Deglet Nour date juice at 50 C, pH ¼ 4 and a ratio pulp: water 1:3. pectinase/100 g and 5 U cellulase/100 g after 120 min (Table 5).…”
Section: Pectinase and Cellulasementioning
confidence: 99%
“…A combination of pectinase and cellulase was used since the synergetic effect of these enzymes is well documented in literature for several fruit such as orange peel, dates and grapefruit peel (Cheikh-Rouhou, Baklouti, et al, 2006;Çinar, 2005;EspachsBarroso, Soliva-Fortuny, & Martín-Belloso, 2005;Wilkins, Widmer, Grohmann, & Cameron, 2007). In this study, the maximum of soluble solids recovery was reached when combining 50 U Table 4 Effect of pectinase and incubation time (min) on soluble solids yield (g of TSS/100 g) in Deglet Nour date juice at 50 C, pH ¼ 4 and a ratio pulp: water 1:3. pectinase/100 g and 5 U cellulase/100 g after 120 min (Table 5).…”
Section: Pectinase and Cellulasementioning
confidence: 99%
“…Membrane fouling is caused mainly by large constituents of the juice such as pectin and polyphenol-protein complexes, which subsequently clog up the membranes. Treatment with enzymes helps to guarantee the complete hydrolysis of pectic substances, to minimize the risk of fouling of the costly membranes [10][11][12][13][14][15] and removal/degradation of polyphenolic compounds that are responsible for haze and sediment formation as well as browning during storage of juice [5,[16][17][18]. There are several studies in which enzyme treatment has been proven to show an improvement in juice clarification and stability over the conventional process.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, date fiber-a by-product of the date processing industry has potential to serve as a functional ingredient to formulate health related food products. Limited studies have been reported in the literature on date-based dietary fibers (Borchani et al, 2011;Elleuch et al, 2008). Nevertheless, the mineral profiles, elemental analysis, particle size had not been characterized before.…”
Section: Introductionmentioning
confidence: 94%
“…30% loss of total produce in Tunisia) due to its inferior quality, damage, and undersized fruit of unattractive appearance (Besbes, Drira, Blecker, Deroanne, & Attia, 2009). It is also reported that dates are also wasted during the sorting, the storage and the conditioning (Cheikh-Rouhou et al, 2006). The non-use of lesser-quality dates for human food constitutes a real economic loss since it is rich in bioactive compounds which can be extracted and used as value added materials (Elleuch et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation